2017
DOI: 10.1002/pc.24499
|View full text |Cite
|
Sign up to set email alerts
|

Novel bioresorbable phosphate glass fiber textile composites for medical applications

Abstract: A manual bench‐top Inkle‐type loom was designed to enable hand woven textiles. These phosphate glass fiber (PGF) textiles, along with unidirectional (UD) fiber mats made from the same batch of yarns, were utilized to manufacture fully resorbable textile composites (T‐C), unidirectional aligned fiber composites (UD‐C), and 0°/90° lay‐up UD fiber‐reinforced composites (0/90‐C). The fiber volume fraction in the composites was set at ∼20%. Retention of flexural properties and mass loss of the composites were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…As can be seen in the SEM (Figure ), there is significant breakdown of the fibers and loss of material with some very small diameter fibers observed. This is in keeping with previous results observed for this fiber type and in composites produced using this fiber type …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As can be seen in the SEM (Figure ), there is significant breakdown of the fibers and loss of material with some very small diameter fibers observed. This is in keeping with previous results observed for this fiber type and in composites produced using this fiber type …”
Section: Resultssupporting
confidence: 93%
“…This is in keeping with previous results observed for this fiber type 19 and in composites produced using this fiber type. 8 Of the samples that could be tested after degradation, there was no significant change in the modulus, which is as expected for a surface eroding material.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…23 In addition, silicate, borate, and phosphate-based GFs have been observed to possess great biological activity, which makes them suitable for the production of fully degradable composites. 24 Notwithstanding, the literature have revealed that the performance of GF reinforced composites is highly dependent on factors such as the aspect ratio of fiber, fiber distribution, fiber content, and fiber-matrix interactions. 25,26 In addition to the shortcomings earlier outlined for PLA, another major issue with its processing is the tendency to degrade during processing as a result of thermal degradation and hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Single filament limits the use of these fibres as they can only be produced as non-woven random or unidirectional fibre mats [24,25]. To overcome this issue and extend application area of PGFs, scale-up manu-facture to multi-filament continuous phosphate glass fibre fabrication needs to be achieved and Zhu et al [26,27] have developed a phosphate glass fibre system P 2 O 5 -B 2 O 3 -CaO-MgO-Na 2 O-Fe 2 O 3 with excellent thermal stability and fibre drawing performance. However, the poor chemical durability of multifilament PGFs in the composite resulted in catastrophic retention of composite mechanical properties during degradation study [27].…”
Section: Introductionmentioning
confidence: 99%